Kelimpahan Jenis dan Persentase Serangan Serangga Hama Pada Budidaya Padi Gogo Dengan dan Tanpa Tumbuhan Berbunga - Yuni Ratna; Wilma Yunita; Elly Indra Swari; Nadia Akmala Zamila (Jurnal Media Pertanian, 2023)
The research was conducted at the research farm and laboratory of plant pest, Faculty of Agriculture, University of Jambi. The aim of the research was to study abundance of types and percentage of insect pest attackin upland rice cultivation using flowering plants. There were two treatments, namely the cultivation of upland rice Inpago 5 variety without and with flowering plants. There were 4 experimental plots with an area of 20 m x 10 m each, 2 plots each for cultivation of upland rice with and without flowering plants. The flowering plants used were sesame (Sesamun indicum) and Tagetes sp which were planted around the experimental plots. Variables observed included the type and number of insect pests, the percentage of rice stem borer attacks and the percentage of grain destroying pests. Data on type, number and percentage of plants attacked by pests were tabulated and analyzed descriptively. The number of pests in upland rice cultivation without flowering plants was more fluctuating and reached a peak at the age of 8 and 10 week after planting. The number of rice stem borers, the percentage of stems attacked by stem borers and the percentage of grains attacked were almost always higher in upland rice cultivation without flowering plants. The results showed that there were more types of insect pests on upland rice plants with flowering plants (27 species) compared to those without flowering plants (17 species). The number of insect pests in upland cultivation without flowering plants fluctuated more than upland rice cultivation with flowering plants. The percentage of insect pest attacks on rice stems and grains was lower in upland rice cultivaton with flowering plants than without flowering plants.